Does preschool education help immigrant children reach their native Peers’ Academic levels? A case of Turkish immigrant children in Sweden - TORAN, MEHMET (My University, 2016)
The disadvantages associated with immigration put the children of immigrant families at risk for academic failure. This study investigates the efficacy of educational support provided by the Swedish preschool system to the children of the Turkish families who migrated to Sweden. In this study non-equivalent control group design was used. The sample of the study consists of a total of 45; 5 years old preschool children, 23 Swedish children and 22 Turkish children receiving native language support. During the research both groups continued attending regular public preschool program. Bracken Basic Concept Scale – Revised Form was used as a data collection tool. The results demonstrated that the Swedish preschool education programme was effective in supporting Swedish and Turkish children’s concept acquisition and school readiness. Nevertheless, the programme was not able to close the gap significantly between the Turkish and Swedish children’s concept acquisition and school readiness observed prior to program implementation.

Göç olgusu ile birlikte ortaya çıkan dezavantajlar göçmen aile çocuklarının akademik başarılarını risk altına almaktadır. Mevcut araştırmada İsveç’e göç etmiş Türklerin çocuklarına İsveç okul öncesi eğitim sisteminde sunulan eğitsel desteğin etkililiği araştırılmaktadır. Araştırmada yöntem olarak eşitlenmemiş kontrol gruplu desen kullanılmıştır. Araştırmanın çalışma grubunu 23’ü İsveçli ve 22’si Türk olup anadili desteği alan 5 yaşında toplam 45 çocuk oluşturmaktadır. Araştırma süresince her iki grupta devlet okuluna devam etmektedir. Araştırmada veri toplama aracı olarak Bracken Temel Kavram ÖlçeğiGözden Geçirilmiş Formu kullanılmıştır. Araştırmanın sonuçları İsveç okul öncesi programının hem İsveç hem de Türk çocukların kavram edinimleri ve okula hazırlık düzeyleri üzerinde etkili olduğunu göstermiştir. Ancak buna rağmen, uygulanan programın Türk ve İsveçli çocukların kavram edinimi ve okula hazırlık bulunuşluk puanları arasındaki farkı kapatamadığı gözlenmiştir.
Okul öncesi eğitim göçmen çocukların yerli akranlarının akademik düzeylerine erişmelerini destekler mi? İsveç’teki göçmen Türk çocuklarının durumu
Keywords: Preschool Education; Immigrant Children; Swedish Preschool Education; School Readiness; Concept Acquisition; Mother Tongue Support; Okul Öncesi Eğitim; Göçmen Çocukları; İsveç Okul Öncesi Eğitimi; Okula Hazırlık; Kavram Edinimi; Anadili Desteği